“ALHS! ALHS! Why Are You So OSINT?” Reading Books During Office Hours (Altre Modernità, 2014)
This is not a story for people who cannot digest acronyms. Indeed, it is as if the secretservices, generally considered, simply could not do without them. If, as many contend,in the term “military intelligence” resonates the echo of an oxymoron, acronyms mayundoubtedly reach the practical goal of saving mental and phonetic energy, killing notless than two birds with a single stone. Applied to secret services and intelligence,acronyms fulfill a double function: they confer an indisputable aura of scientific dignityto what they aim at referring to, and they conceal behind a succession of usually eeriecapital letters what they also intend to reveal.